Risk management practices of local commercial banks in Sabah / Lauris Abidin - Abidin, Lauris (2011)
This study aims to examine the extent to which local commercial banks in Sabah use Risk Management Practices (RMPs) and techniques in dealing with various types of risks. In this globalization era, risk management is now becoming a critical issue where new risks continue to emerge while the current has never disappeared. Therefore, there is a need to do continuous research in the issue of risk management. This study will cover the six aspects in risk management practices (RMPs) including Understanding Risk and Risk Management (URM), Risk Identification (RI), Risk Assessment and Analysis (RAA), Risk Monitoring (RM), Risk Management Practices (RMPs), and Credit Risk Analysis (CRA). The survey used modified questionnaire which addressed these six aspects. Using the Statistical Package for Social Science (SPSS), the results were then analysed. The findings of the study were commercial banks in Sabah has clearly understand risk and risk management, commercial banks in Sabah are reasonably efficient in risk assessing and analyzing and have efficiently monitoring their risk.